9.1 – Multiplying & Dividing Rational Expressions
Ex. 1 Simplify. a. 30bc 12b 2
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 12b 2
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = x 2 – 4x – 5
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = x 2 – 4x – 5
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1) = 2x x + 1
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 5b 16a 3
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b = 3·b 2·2·a·a
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b = 3·b = 3b 2·2·a·a 4a 2
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = x 2 + 4x + 3 x – 2
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2) x 2 + 4x + 3 x – 2
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1) (x – 2)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2) = 3(x + 4) (x + 3)
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2) = 3(x + 4) = 3x + 12 (x + 3) x + 3
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 15a 3 b 3 5ab 3
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y 15a 3 b 3 5ab 3 15a 3 b 3
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y = 2·x 3·a·a·y
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y = 2·x = 2x 3·a·a·y 3a 2 y
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 – 9 x + 3
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12 x 2 – 9 x + 3 x 2 – 9
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3) (x + 3)(x – 3)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2) = x + 4 x + 2